Acquisition helps Cooper Standard expand its product range and capabilities. Issue 7 (July 2018) - Unknown
Abstract : Cooper Standard, a US supplier of systems and components for the automotive industry, including rubber and plastic sealing components, has acquired 80.1% of the automotive parts business of LS Mtron in a move which, it says, will enhance its automotive product range and capabilities.